S120 Metabolic dysfunction in pulmonary arterial hypertension and response to exercise therapy. (December 2018) - MacKenzie, A; Irvine, V; Jayasekera, G; McCaughy, P; Ford, J; Crowe, T; Welsh, D; Wilson, K; Brewis, M; Johnson, M; Church, C
Abstract : Introduction: A pro-inflammatory phenotype, with evidence of metabolic dysfunction is increasingly being recognised as a distinct entity in Pulmonary Arterial Hypertension (PAH). Current disease targeted therapy in PAH is limited to pulmonary artery vasodilators, with no specific therapy to target the extra-pulmonary manifestations of the disease. It is unclear if metabolic dysfunction and inflammation are modifiable in PAH and how they relate to disease severity. Aims: Explore the incidence of metabolic dysfunction in a well phenotyped PAH cohort Investigate the potential of exercise therapy to modify metabolic dysfunction in PAH. Methods: 23 PAH patients participating in an exercise rehabilitation study at the Scottish Pulmonary Vascular Unit between 2015 and 2018 were included. Those who had known diabetes were excluded. Serum was taken before, during and after a 15 week aerobic and resistance PAH specific exercise rehabilitation programme, along with standard tests to assess PAH severity including Cardiopulmonary Exercise Testing (CPET) and 6 min walk distance (6 MWD). No specific dietary intervention was performed. Fasting serum C-peptide, glucose and the HOMA-IR score were used to assess insulin resistance. CRP, Neutrophil to Lymphocyte Ratio (NLR) and Platelet to Lymphocyte Ratio (PLR) were calculated as basic markers of systemic inflammation. Results: 47.8% (11/23) of patients participating in the exercise programme had fasting C-peptide above the normal range. Median HOMA-IR score was 2.2 (range 0.5–4.65). The median age was 50.2 (37–74), Male 5/23 (22%), BMI 29.7 (19–41). 22% (6/23) had CTD-PAH, 4% (1/23) inoperable CTEPH and the remainder IPAH. Those with a raised C-peptide had poorer WHO Functional Class (FC), higher indices of inflammation and a trend to poorer exercise capacity (table 1). Following exercise therapy, there was no significant reduction in C-peptide, 1.05 (0.5) to 1.01 (0.6), p 0.879 or HOMA IR score, 2.24 (1.1) to 2.19 (1.3), p 0.867. Conclusion: In a small well phenotyped PAH cohort, there was a high incidence of metabolic dysfunction. This was associated with markers of reduced exercise capacity and systemic inflammation. Following exercise therapy, there were no significant improvements in serum markers of insulin resistance in this cohort. Dedicated studies are required to determine the mechanisms leading to metabolic dysfunction and inflammation in PAH, in order to develop suitable therapeutic strategies.